Coated steel sheet
A plated steel sheet with a tailored composition and intermetallic compounds addresses the issue of low corrosion resistance in varying pH conditions, providing enhanced durability across acidic and alkaline environments.
Patent Information
- Application Number
- CN202280070881.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-26
- Filing Date
- 2022-08-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-08-16
AI Technical Summary
Existing plated steel sheets exhibit low corrosion resistance in both acidic and alkaline environments, limiting their application range.
A plated steel sheet with a specific chemical composition and X-ray diffraction patterns, containing elements like Al, Mg, Sn, Bi, In, Ca, and others, forming intermetallic compounds to enhance corrosion resistance across varying pH conditions.
The steel sheet achieves high corrosion resistance in both acidic and alkaline environments, ensuring durability and wide applicability.
Smart Images

Figure BDA0004802478200000043 
Figure BDA0004802478200000371 
Figure BDA0004802478200000381
Abstract
Description
Technical Field
[0001] The invention relates to a plated steel sheet.
[0002] This application claims priority based on Japanese patent application No. 2021-174676 filed on October 26, 2021, and its contents are cited here. Background Art
[0003] Plated steel sheets can be used in a variety of building materials industries. Since the life of a building depends on the rate of loss of the coating, it is best to use highly corrosion-resistant plated steel sheets as building materials. For example, as steel sheets showing high corrosion resistance, the plated steel sheets described in Patent Documents 1 to 3 are known.
[0004] There are various environments in Japan. In areas where volcanic gas occurs and industrial areas, SOx gas in the atmosphere dissolves into rainwater and becomes acid rain, which sometimes seriously damages the life of the plated steel sheet. Generally speaking, the Al-based plated steel sheet known as Galvalume steel sheet (registered trademark) has good corrosion resistance in acidic environments, but low corrosion resistance in alkaline environments. Therefore, the corrosion resistance and sacrificial anode corrosion resistance of Al-based plated steel sheets in alkaline environments such as ammonia atmospheres generated in composting houses such as cow sheds and pig sheds are low, so its scope of use is limited.
[0005] Therefore, although the application range of Zn-based plated steel sheets as shown in Patent Documents 1 to 3 is wide, the corrosion resistance of Zn-based plated steel sheets in acidic environments tends to be lower than that of Al-based plated steel sheets, and there has been a demand for improving the corrosion resistance in acidic environments. In other words, as plated steel sheets, there has been a demand for plated steel sheets that show high corrosion resistance in all regions from the acidic side to the alkaline side.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 10-226865
[0009] Patent Document 2: International Publication No. 2000 / 71773
[0010] Patent Document 3: International Publication No. 2018 / 139619 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a plated steel sheet that exhibits high corrosion resistance in an acidic to alkaline environment.
[0013] Means for solving problems
[0014] [1] A plated steel sheet having a plated layer on a surface of the steel sheet,
[0015] The average chemical composition of the coating contains, in mass %,
[0016] Al: more than 15.0% and less than 30.0%,
[0017] Mg: more than 5.0% and less than 15.0%,
[0018] Sn: 0~0.70%,
[0019] Bi: 0~0.35%,
[0020] In: 0~0.35%,
[0021] Ca: 0.03-0.60%,
[0022] Y: 0~0.30%,
[0023] La: 0~0.30%
[0024] Ce: 0~0.30%,
[0025] Si: 0.01-0.75%,
[0026] Cr: 0~0.25%,
[0027] Ti: 0~0.25%,
[0028] Ni: 0-1.00%,
[0029] Co: 0-0.25%,
[0030] V: 0~0.25%,
[0031] Nb: 0~0.25%,
[0032] Cu: 0-0.25%,
[0033] Mn: 0~0.25%,
[0034] Fe: 0-5.0%,
[0035] Sr: 0~0.5%,
[0036] Sb: 0-0.5%,
[0037] Pb: 0~0.5%,
[0038] B: 0~0.5%
[0039] Li: 0~0.5%
[0040] Zr: 0~0.5%,
[0041] Mo: 0~0.5%,
[0042] W: 0~0.5%,
[0043] Ag: 0-0.5%, and
[0044] P: 0~0.5%,
[0045] The remainder includes Zn and impurities;
[0046] The total amount ΣA of Sn, Bi and In is 0% or more and less than 0.75%,
[0047] The total amount of Ca, Y, La and Ce ΣB is 0.03 to 0.60%,
[0048] The total amount ΣC of Cr, Ti, Ni, Co, V, Nb, Cu and Mn is 0 to 1.00%,
[0049] Satisfy Sn≤Si and 20.0≤Mg / Si;
[0050] In the X-ray diffraction pattern of the surface of the coating layer measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the following formulas (1) to (6) define the X-ray diffraction patterns of Al 2.15 Zn 1.85 In the case of I1 to I3 obtained from the X-ray diffraction peak of Ca, I4 obtained from the X-ray diffraction peak of CaZn2, and I5 and I6 obtained from the X-ray diffraction peak of η'-MgZn2, the following formulas (A) and (B) are satisfied:
[0051] [Mathematical formula 1]
[0052]
[0053]
[0054]
[0055]
[0056]
[0057]
[0058] 4.05≤I1+I2+I3+I4 (A)
[0059] 2.05≤I5+I6 (B)
[0060] In the above formulas (1) to (6), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (1) to (6), respectively.
[0061] [2] The plated steel sheet according to [1] above, wherein
[0062] The average chemical composition of the coating satisfies 20.0≤Mg / Si≤38.0 and 3.00≤Al / Mg≤4.00;
[0063] In the X-ray diffraction spectrum of the surface of the coating measured using Cu-Kα rays at an X-ray output of 40 kV and 150 mA, when I7 to I9 obtained from the X-ray diffraction peaks of MgAlSi are defined by the following equations (7) to (8), the following equation (C) is satisfied:
[0064] [Mathematical formula 2]
[0065]
[0066]
[0067]
[0068] 3.05≤I7+I8+I9 (C)
[0069] Among them, in the above formulas (7) to (9), Imax(k~m°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between k and m°, I(n°) is the X-ray diffraction intensity when the diffraction angle 2θ is at n°, and k, m, and n are the diffraction angles 2θ shown in formulas (7) to (9), respectively.
[0070] [3] The plated steel sheet according to [1] or [2] above, wherein
[0071] The average chemical composition of the coating satisfies 0.01≤Sn;
[0072] In the X-ray diffraction spectrum of the surface of the coating measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I calculated from the X-ray diffraction peak of Mg9Sn5 is defined by the following formula (10): 10 In the case of, the following formula (D) is satisfied:
[0073] [Mathematical formula 3]
[0074]
[0075] 1.04≤I 10 (D)
[0076] Wherein, in the formula (10), Imax(23.10~23.80°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 23.10 and 23.80°, I(23.10°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.10°, and I(23.80°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.80°.
[0077] [4] The plated steel sheet according to any one of [1] to [3] above, wherein in the X-ray diffraction pattern of the surface of the plated layer measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I peaks determined from the X-ray diffraction peaks of the metal oxides defined by the following formulas (11) to (13) are: 11 ~I 13 In the case of, the following formula (E) is satisfied:
[0078] [Formula 4]
[0079]
[0080]
[0081]
[0082] 3.04≤I 11 +I 12 +I 13 (E)
[0083] In the above formulas (11) to (13), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (11) to (13), respectively.
[0084] [5] The plated steel sheet according to any one of [1] to [4] above, wherein the plated layer contains a Zn phase, an Al phase, an Al—Zn phase, an η′-MgZn 2 phase, and a MgZn 2 phase.
[0085] Effects of the Invention
[0086] According to the present invention, it is possible to provide a plated steel sheet that exhibits high corrosion resistance in an acidic to alkaline environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 It is a schematic diagram for explaining the formula (1). DETAILED DESCRIPTION
[0088] If Zn phase and Al phase exist as single metal phases in the coating, the properties of amphoteric metals are likely to appear in the coating. In addition, the corrosion resistance of the coating can be changed by changing the existence form of the phases contained in the coating. In addition, Al and Zn are easy to fuse with each other in the coating because of the similarity in atomic radius. Therefore, in the coating containing Zn and Al, in addition to the Zn phase and the Al phase, the Al-Zn phase (Al: 15-25% by mass, preferably containing about 20% by mass of Al) is easy to form. However, the Zn phase and the Al-Zn phase are phases with low corrosion resistance, especially in acidic and alkaline environments, and therefore it is necessary to reduce the content of these phases. In addition, the phase containing Mg generally has higher corrosion resistance in alkaline environments, but not too high in acidic environments.
[0089] The inventors have found that in order to improve the corrosion resistance in an acidic environment, it is effective to remove the Al-Zn phase, reduce the amount of the Zn phase, or contain other additive elements to form an intermetallic compound containing Al and Zn. In particular, regarding the intermetallic compound, the inventors have found that in the Al-Zn phase, Zn and Al are usually in a state of forming fine single phases and separating the two phases, so it is effective to contain the Ca element in the coating as an element that produces the intermetallic compound of Zn and Al. By containing Ca in the coating, a Ca-Al-Zn compound is formed, and the Al-Zn phase containing fine Zn phase and Al phase is reduced. The Ca-Al-Zn compound is a compound with a higher natural potential than Al, and the corrosion rate is lower than that of the Al phase, so it can improve the corrosion resistance.
[0090] On the other hand, if the corrosion resistance in an acidic environment is improved by reducing the amount of the Zn phase in the coating, the corrosion resistance in an alkaline environment is reduced. As a countermeasure, it is conceivable to reduce the Al phase. Since the corrosion resistance in an alkaline environment is improved by reducing the Al phase, it is possible to prevent the corrosion resistance in an alkaline environment from deteriorating due to the reduction of the Zn phase.
[0091] In order to improve the corrosion resistance in alkaline environment, it is possible to remove the Al-Zn phase or increase the MgZn2 phase containing Mg. The MgZn2 phase has good corrosion resistance in alkaline environment. In addition, in order to further improve the corrosion resistance in alkaline environment, it is preferred to introduce a compound with better alkali corrosion resistance than the MgZn2 phase into the coating.
[0092] As such a compound, η'-MgZn2 phase having a different crystal structure from the MgZn2 phase can be cited. The η'-MgZn2 phase has high corrosion resistance, especially in alkaline environments. In addition, even if the MgZn2 phase is transformed into the η'-MgZn2 phase, there is no increase or decrease in the amount of elements, so it is possible to improve the corrosion resistance in an alkaline environment without damaging the corrosion resistance in an acidic environment. In this way, by containing the MgZn2 phase and the η'-MgZn2 phase, a coating layer that improves corrosion resistance in both an acidic environment and an alkaline environment can be formed. The following is a description of the plated steel sheet involved in an embodiment of the present invention.
[0093] The plated steel sheet according to the embodiment of the present invention (hereinafter referred to as the plated steel sheet according to the present embodiment) is a plated steel sheet having a plated layer on the surface of the steel sheet, wherein the average chemical composition of the plated layer contains, by mass%, Al: more than 15.0% and less than 30.0%, Mg: more than 5.0% and less than 15.0%, Sn: 0 to 0.70%, Bi: 0 to 0.35%, In: 0 to 0.35%, Ca: 0.03% and less than 0.1%, and Cu: 0.03% and less than 0.1%, respectively. ~0.60%, Y: 0~0.30%, La: 0~0.30%, Ce: 0~0.30%, Si: 0.01~0.75%, Cr: 0~0.25%, Ti: 0~0.25 %, Ni: 0~1.00%, Co: 0~0.25%, V: 0~0.25%, Nb: 0~0.25%, Cu: 0~0.25%, Mn: 0~0.25%, Fe: 0~5 .0%, Sr: 0-0.5%, Sb: 0-0.5%, Pb: 0-0.5%, B: 0-0.5%, Li: 0-0.5%, Zr: 0-0.5%, Mo: 0-0.5%, W: 0-0.5%, Ag: 0-0.5% and P: 0-0.5%, the remainder includes Zn and impurities; the total amount of Sn, Bi and In ΣA is 0% or more and less than 0.75%, Ca, Y, The total amount ΣB of La and Ce is 0.03-0.60%, the total amount ΣC of Cr, Ti, Ni, Co, V, Nb, Cu and Mn is 0-1.00%, and Sn≤Si and 20.0≤Mg / Si are satisfied; in the X-ray diffraction spectrum of the surface of the coating measured by Cu-Kα ray at an X-ray output of 40 kV and 150 mA, the following formulas (1) to (6) are used to define the X-ray diffraction pattern from Al 2.15 Zn 1.85 In the case of I1 to I3 obtained from the X-ray diffraction peak of Ca, I4 obtained from the X-ray diffraction peak of CaZn2, and I5 and I6 obtained from the X-ray diffraction peak of η'-MgZn2, the following formulas (A) and (B) are satisfied:
[0094] [Formula 5]
[0095]
[0096]
[0097]
[0098]
[0099]
[0100]
[0101] 4.05≤I1+I2+I3+I4 (A)
[0102] 2.05≤I5+I6 (B)
[0103] In the above formulas (1) to (6), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (1) to (6), respectively.
[0104] In the following description, the expression "%" of the content of each element in the chemical composition means "mass %". In addition, the numerical range expressed by "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit. In addition, the numerical range with "exceeding" or "lower than" means a range not including these numerical values as the lower limit or the upper limit.
[0105] In addition, the so-called "corrosion resistance" refers to the property that the plated steel sheet is difficult to corrode. The Zn-based coating has a sacrificial anode corrosion protection effect on the steel material. In the corrosion process of the plated steel sheet with the Zn-based coating, the coating is corroded and white rusted before the steel sheet corrodes. After the white rusted coating disappears, the steel sheet corrodes to generate red rust.
[0106] The steel sheet to be plated will be described.
[0107] The shape of the steel plate is mainly a plate, but its size is not particularly limited. The plated steel plate formed with a coating on the plate is a plated steel plate manufactured by a conventional hot-dip galvanizing process, and the plated steel plate manufactured by a process such as a continuous hot-dip galvanizing line (CGL) and an intermittent hot-dip galvanizing process in which the steel plate is immersed in a molten metal and then solidified fits this category. By processing (including welding) and combining the plated steel plates manufactured by such a method, various products can be processed and steel structural parts with excellent corrosion resistance can be manufactured.
[0108] There are no particular restrictions on the original plate material of the steel plate. For example, the hot-rolled steel plate shown in JIS G3193: 2019 and the cold-rolled steel plate shown in JIS G3141: 2021 are the most common steel plates as the original plate for plating. In addition, for example, various steel plates such as ordinary steel (SS material (rolled steel for ordinary structure)), pre-plated steel made of various metal thin plating (JIS G3302: 2019), aluminum-killed steel, ultra-low carbon steel, high carbon steel, various high-strength steels (JIS G3135: 2018), and some high-alloy steels (steel containing corrosion resistance strengthening elements such as Ni and Cr JIS G3114: 2016, etc.) are suitable for use. In addition, the steel plate has no particular restrictions on conditions such as the steelmaking method of the steel material (blast furnace steel, electric furnace steel), the manufacturing method of the steel plate (hot rolling method, pickling method, cold rolling method, etc.). In addition, when using a steel sheet material that is difficult to plate, a pre-plated steel sheet may be used, which is pre-plated with a coating of Zn, Ni, Sn, Fe or an alloy system composed of these elements with a thickness of less than 30 μm on the surface of the steel sheet. If such a pre-plated steel sheet is used, when immersed in a plating bath, the metal elements in the pre-plating layer are replaced by the metal elements of the plating bath, which can solve the problem of non-plating (the area where the plating metal cannot be attached due to an oxide film, etc.).
[0109] Next, the coating is described. The coating involved in the present embodiment includes a Zn-Al-Mg alloy layer. If alloy elements such as Al and Mg are added to Zn, the corrosion resistance can be improved, so it can have the same corrosion resistance as a thin film, such as about half of a conventional Zn coating. Therefore, in the present embodiment, the corrosion resistance equal to or higher than that of a conventional Zn coating is also ensured by the thin film coating. In addition, the coating may also include an Al-Fe alloy layer.
[0110] The Zn-Al-Mg alloy layer is composed of a Zn-Al-Mg alloy, which is a ternary alloy containing Zn, Al, and Mg.
[0111] The Al-Fe alloy layer is an interface alloy layer between the steel plate and the Zn-Al-Mg alloy layer.
[0112] That is to say, the coating involved in this embodiment can be a single-layer structure of a Zn-Al-Mg alloy layer, or a laminated structure including a Zn-Al-Mg alloy layer and an Al-Fe alloy layer. In addition, as a coating substrate, when a pre-plated material coated with a metal having a high melting point (more than 600°C) is used, depending on the original coating thickness, a layer containing the metal layer is sometimes left on the Fe surface with a thickness less than 1 μm, or a trace is left in some form as a replacement body of an Al-Fe intermetallic compound. The metal melted near the plating bath temperature hardly leaves its trace. In the case of a laminated structure, it is best to use a Zn-Al-Mg alloy layer as a layer constituting the coating surface. However, an oxide film of the coating constituent elements is sometimes formed on the outermost surface of the coating with a thickness less than 1 μm. Usually, the elements contained in the coating are combined with oxygen on the coating surface, so there is an oxide film of a thin film, and the bonds such as Zn-O, Mg-O, Al-O, Si-O, and Ca-O can be confirmed by surface analysis such as XPS (X-ray spectrometry). There is a tendency that relatively easily oxidizable elements are more likely to be present on the plated surface.
[0113] In the case where the coating is a laminated structure including a Zn-Al-Mg alloy layer and an Al-Fe alloy layer, the steel material and the Zn-Al-Mg alloy layer are combined through the Al-Fe alloy layer. The thickness of the interface alloy layer can be controlled by the coating bath temperature and the coating bath immersion time during the manufacture of the plated steel sheet. In the manufacturing method of the hot-dip galvanized steel sheet centered on the Sendzimir method, since the Zn-Al-Mg alloy layer becomes the main body of the coating, the thickness of the Al-Fe alloy layer is very thin, so the effect on the corrosion resistance of the coating is small, and it is formed near the interface, so it has almost no effect on the corrosion resistance in the initial stage of corrosion and the appearance of the coating.
[0114] When forming displacement plating such as two-stage plating or pre-plating, depending on the thickness of the pre-plating layer, the elements contained in the pre-plating layer are sometimes contained in the Al-Fe alloy layer. On the Fe surface, the pre-plating layer remains after plating, and sometimes an interface alloy layer is formed. In addition, the diffusion of the plating element is very active. If the plating component diffuses to the Fe side, an Al-Fe alloy layer is sometimes formed under the pre-plating layer, which sometimes occurs locally due to reactivity, and its position cannot be strictly defined, but the performance changes caused by these layers are not large because of the thin thickness.
[0115] Furthermore, the thickness of the entire coating is not particularly limited because it is affected by the coating conditions. In addition, the thickness of the entire coating depends on the viscosity and specific gravity of the coating bath in the conventional hot dip coating method. In addition, the coating amount per unit area can be adjusted according to the drawing speed of the steel sheet (plated original sheet) and the strength of the frictional contact. The maximum value of the coating thickness formed in the conventional hot dip coating method is mostly less than 100 μm in continuous hot dip coating and is mostly less than 200 μm in intermittent coating.
[0116] The Al-Fe alloy layer is formed on the surface of the steel plate (specifically, between the steel plate and the Zn-Al-Mg alloy layer), and is a layer with Al5Fe2 phase as the main phase as the structure. The Al-Fe alloy layer is formed by mutual atomic diffusion of the base metal (steel plate) and the plating bath. When the hot dip plating method is used as the method for forming the plating layer, the Al-Fe alloy layer is easily formed in the plating layer containing the Al element. In the manufacturing method described below, since the plating bath contains Al above a certain concentration, the Al5Fe2 phase is formed most. However, if the interface alloy layer is combined with Al, a solid phase occurs in the plating bath. Unlike a liquid such as a plating bath, the diffusion of Al and Fe atoms in the intermetallic compound takes time, so a speed control stage of the concentration of Al and Fe components is generated near the interface alloy layer. Therefore, multiple intermetallic compounds with different atomic ratios are formed in the Al-Fe alloy layer, and generally speaking, the closer to the interface, the higher the Fe concentration. However, depending on the diffusion conditions, there are sometimes temporary layers with low Al and Fe components inside the Al-Fe layer. Therefore, the Al-Fe alloy layer sometimes contains a small amount of AlFe phase, Al3Fe phase, etc. in addition to the Al5Fe2 phase. In addition, since the plating bath also contains Zn at a fixed concentration, the Al-Fe alloy layer also contains a small amount of Zn. In addition, the Al-Fe alloy layer also contains a small amount of Si that easily aggregates at the interface.
[0117] When Si is contained in the plating layer, Si is particularly easy to be incorporated into the Al-Fe alloy layer, so the Al-Fe alloy layer sometimes becomes an Al-Fe-Si intermetallic compound phase. As an intermetallic compound phase identified in the Al-Fe-Si intermetallic compound phase, there is an AlFeSi phase, and as isomers, there are α, β, q1, q2-AlFeSi phases. Therefore, these AlFeSi phases are sometimes detected in the Al-Fe alloy layer. The layer containing these AlFeSi phases is called an Al-Fe-Si alloy layer.
[0118] That is, the plating layer involved in this embodiment can be composed of a Zn-Al-Mg alloy layer, a Zn-Al-Mg alloy layer and an Al-Fe alloy layer, or a Zn-Al-Mg alloy layer and an Al-Fe-Si alloy layer. Furthermore, it is inevitable that Zn, etc., whose atomic radius is close to that of Al, is partially incorporated into the Al-Fe alloy layer as a substitution body, and it is inevitable that transition metals Ni, Cr, Co, etc., whose atomic radius is close to that of Fe, are incorporated into these intermetallic compounds as substitution bodies, but the main structure can be treated as an Al-Fe alloy layer.
[0119] Next, the average chemical composition of the coating is described. Regarding the average chemical composition of the entire coating, when the coating is a single-layer structure of a Zn-Al-Mg alloy layer, it is the average chemical composition of the Zn-Al-Mg alloy layer. In addition, when the coating is a laminated structure of an Al-Fe alloy layer and a Zn-Al-Mg alloy layer, it is the total average chemical composition of the Al-Fe alloy layer and the Zn-Al-Mg alloy layer. In addition, when the coating is a laminated structure of an Al-Fe-Si alloy layer and a Zn-Al-Mg alloy layer, it is the total average chemical composition of the Al-Fe-Si alloy layer and the Zn-Al-Mg alloy layer.
[0120] Usually, in the hot-dip plating method, the chemical composition of the Zn-Al-Mg alloy layer is roughly the same as the plating bath because most of the formation reaction of the plating layer ends in the plating bath. In addition, in the hot-dip plating method, the Al-Fe alloy layer is formed and grown instantly after being immersed in the plating bath. Then, the Al-Fe alloy layer is in the plating bath or after being lifted from the plating bath, and the formation and growth reaction are terminated by the subsequent plating solidification reaction until it reaches about 550°C, and its thickness is also mostly thin relative to the Zn-Al-Mg alloy layer. Therefore, as long as no special heat treatment such as heating alloying treatment is performed after plating, the average chemical composition of the entire plating layer is essentially equal to the chemical composition of the Zn-Al-Mg alloy layer, and the composition of the Al-Fe alloy layer can be ignored. The Al-Fe-Si alloy layer is also the same as the Al-Fe alloy layer, and the composition of the Al-Fe-Si alloy layer can be ignored.
[0121] First, elements contained in the plating layer according to the present embodiment will be described.
[0122] Al: more than 15.0% and less than 30.0%
[0123] Al and Zn are also elements that constitute the main body of the coating. In Zn-Al-Mg plating, Al phase is mainly formed in the coating. If the Al content is less than 15.0%, the corrosion resistance in an acidic environment is not sufficient. Therefore, the Al content is set to more than 15.0%, preferably more than 18.0%, and more preferably more than 20%. On the other hand, if the Al content exceeds 30.0%, the corrosion resistance in an alkaline environment is not sufficient. Therefore, the Al content is set to less than 30.0%, preferably less than 25.0%. Furthermore, if the Al content in the coating increases, the Zn content is relatively reduced, and the sacrificial anode corrosion resistance decreases. Therefore, as a plated steel sheet, in order to ensure the sacrificial anode corrosion resistance, the Al content should be set to more than 15.0% and less than 30.0%. However, if it is this composition range, an Al-Zn phase (a phase containing about 20% by mass of Al) with low corrosion resistance is formed. Therefore, in this embodiment, the Al-Zn phase is reduced by adopting the manufacturing method described later. This makes it easy to improve the corrosion resistance and ensure the corrosion resistance in an acidic environment and an alkaline environment.
[0124] Mg: more than 5.0% and less than 15.0%
[0125] Mg is an element constituting the main body of the plating layer, similarly to Zn. If Mg is insufficient, the corrosion resistance in an alkaline environment tends to decrease, so the Mg content is set to more than 5.0%, preferably more than 7.0%. On the other hand, if the Mg content exceeds 15.0%, the corrosion resistance in an acidic environment deteriorates. Therefore, the Mg content is set to 15.0%. It is preferably 13.0% or less, and more preferably 10.0% or less.
[0126] Element Group A
[0127] Sn: 0~0.70%
[0128] Bi: 0~0.35%
[0129] In: 0~0.35%
[0130] Total amount of Sn, Bi and In ΣA: 0% or more and less than 0.75%
[0131] Each element of element group A (Sn, Bi, In) is an element that can be contained arbitrarily, so the content of each is set to 0% or more. In addition, Sn is an essential element for forming Mg9Sn5 that can greatly improve the corrosion resistance of the plating layer in acidic and alkaline environments. Since the minimum Sn content required to form Mg9Sn5 is 0.01%, the Sn content can also be set to 0.01% or more.
[0132] In addition, elements that show the same effect as Sn include Bi and In, which can form intermetallic compounds that improve corrosion resistance in alkaline environments. As such intermetallic compounds, Bi2Mg3, InMg3, etc. are suitable. Since Sn, Bi, and In form mutual substitution bodies, Sn can be contained in an amount of less than 0.70%, and Bi and In can be contained in an amount of less than 0.35%, respectively. The elements of element group A have an effect on corrosion resistance in alkaline environments, but if the content of these elements exceeds the upper limit, the corrosion resistance in acidic environments is extremely deteriorated.
[0133] In addition, even if the total amount of the elements of the element group A is excessive, the corrosion resistance in an acidic environment is deteriorated, so the total amount ΣA of Sn, Bi and In is set to be greater than 0% and less than 0.75%. The total amount ΣA is preferably less than 0.01%, more preferably less than 0.05%, and further preferably greater than 0.10%. In addition, the total amount ΣA is preferably less than 0.60%, more preferably less than 0.50%.
[0134] It should be noted that the total amount ΣA of Sn, Bi, and In refers to the total content of Sn, Bi, and In.
[0135] Element Group B
[0136] Ca: 0.03~0.60%
[0137] Y: 0~0.30%
[0138] La: 0~0.30%
[0139] Ce: 0~0.30%
[0140] Total amount of Ca, Y, La and Ce ΣB: 0.03~0.60%
[0141] Ca is not the main element in the coating, but it is important for the formation of Al 2.15 Zn 1.85 Ca is an essential element. In addition, Ca is also an essential element for forming CaZn2. Therefore, the minimum Ca content required to form these intermetallic compounds is 0.03% or more, so the Ca content is set to 0.03% or more. The corrosion resistance in acidic and alkaline environments is improved by containing these intermetallic compounds. The Ca content is preferably 0.05% or more, more preferably 0.10% or more, and further preferably 0.20% or more. On the other hand, if the Ca content exceeds 0.60%, the corrosion resistance in acidic and alkaline environments deteriorates. Therefore, the Ca content is set to less than 0.60%, preferably less than 0.50%, and more preferably less than 0.40%.
[0142] Elements that play the same role as Ca include Y, La, and Ce. Since these elements are arbitrarily added elements, their respective contents are set to be above 0%. These elements have a tendency to replace Ca. However, in the absence of Ca, even if Y, La, and Ce are contained, sufficient performance cannot be exerted. After Ca is contained in the above-mentioned content, by containing Y, La, and Ce in a range of less than 0.30%, they form mutually substituted bodies and improve the corrosion resistance in an alkaline environment. However, if Y, La, and Ce each exceed 0.30%, the corrosion resistance in an alkaline environment is extremely deteriorated. Therefore, the contents of Y, La, and Ce are each set to be less than 0.30%.
[0143] In addition, even if the total amount of the elements of the element group B is excessive, the corrosion resistance in an alkaline environment is deteriorated, so the total amount ΣB of Ca, Y, La and Ce is set to 0.03-0.60%. The total amount ΣB is preferably 0.05% or more, more preferably 0.10% or more, and further preferably 0.20% or more. In addition, the total amount ΣB is preferably 0.50% or less, and more preferably 0.40% or less.
[0144] It should be noted that the total amount ΣB of Ca, Y, La and Ce is the total content of Ca, Y, La and Ce.
[0145] Si: 0.01~0.75%
[0146] Si is an essential element for forming intermetallic compounds in the coating. The coating composition in this embodiment has a high melting point and the operating temperature reaches about 500°C during hot dip coating. If it is this operating temperature, when the steel sheet is immersed in the coating bath, Al and Zn actively diffuse with Fe to form intermetallic compounds, but Si can inhibit this excessive reaction. As long as the Si content is more than 0.01%, the diffusion reaction of Fe can be greatly inhibited, and it becomes easy to control the formation of intermetallic compounds contained in the coating. However, if the Si content is less than 0.01%, the coating composition is uneven due to the excessive diffusion of Fe in the coating, and the corrosion resistance in acidic and alkaline environments is extremely deteriorated. Therefore, the Si content is set to more than 0.01%. Preferably, it is more than 0.10%, and more preferably more than 0.20%. Even if the Si content is excessive, the corrosion resistance in acidic and alkaline environments is deteriorated by combining Si with the constituent elements of the coating, so the Si content is set to less than 0.75%. It is preferably 0.50% or less, and more preferably 0.40% or less.
[0147] Furthermore, Si is an element that is very easy to combine with Ca, for example, it is easy to form various Al-Ca-Si compounds such as CaAlSi, Al2CaSi2, Ca2Al4Si3, Ca2Al3Si4, etc. In this embodiment, in order to ensure corrosion resistance in an acidic environment and an alkaline environment, it is best to produce free Ca, but if the Si content is high, it becomes easy to form these intermetallic compounds.
[0148] Element Group C
[0149] Cr: 0~0.25%
[0150] Ti: 0~0.25%
[0151] Ni: 0~1.00%
[0152] Co: 0~0.25%
[0153] V: 0~0.25%
[0154] Nb: 0~0.25%
[0155] Cu: 0~0.25%
[0156] Mn: 0~0.25%
[0157] Total amount of Cr, Ti, Ni, Co, V, Nb, Cu and Mn ΣC: 0~1.00%
[0158] Since the elements of element group C are arbitrary added elements in the plating layer, the content of each is set to 0% or more. These metals have a tendency to replace with Al, Zn, etc. in the plating layer, and the potential moves to the high side, and have a tendency to improve the corrosion resistance in an acidic environment by containing the above-mentioned content range. The excessive content of these elements deteriorates the corrosion resistance in an acidic environment and an alkaline environment due to the formation of intermetallic compounds containing these elements. Therefore, the content of Cr, Ti, Co, V, Nb, Cu, and Mn is set to 0.25% or less. In addition, the Ni content is set to 1.00% or less. In addition, if the total amount of element group C is excessive, the corrosion resistance in an acidic environment and an alkaline environment is deteriorated, so the total amount ΣC of Cr, Ti, Ni, Co, V, Nb, Cu and Mn is set to 1.00% or less. The total amount ΣC is preferably 0.80% or less, and more preferably 0.50% or less.
[0159] It should be noted that the total amount ΣC of Cr, Ti, Ni, Co, V, Nb, Cu and Mn refers to the total content of Cr, Ti, Ni, Co, V, Nb, Cu and Mn.
[0160] Fe: 0-5.0%
[0161] The plated steel sheet involved in this embodiment is a hot-dip plated steel sheet, so Fe sometimes diffuses from the steel sheet (plated original sheet) into the plated layer during manufacturing. Sometimes the plated layer contains up to 5.0% Fe, but the change in corrosion resistance based on the inclusion of this element cannot be confirmed. Therefore, the Fe content is set to 0 to 5.0%.
[0162] Element Group D
[0163] Sr: 0~0.5%
[0164] Sb: 0~0.5%
[0165] Pb: 0~0.5%
[0166] B: 0~0.5%
[0167] Li: 0~0.5%
[0168] Zr: 0~0.5%
[0169] Mo: 0~0.5%
[0170] W: 0~0.5%
[0171] Ag: 0~0.5%
[0172] P: 0~0.5%
[0173] Since the elements of element group D are optional additive elements that can also be contained in the plating layer, the content of each element is set to 0% or more. These elements have the same effects as the elements of element group C described above, and are elements that are easier to contain than element group C. Therefore, the content of each element of element group D is set to 0 to 0.5%. The total amount ΣD of Sr, Sb, Pb, B, Li, Zr, Mo, W, Ag and P can also be set to 0 to 0.5%.
[0174] Furthermore, the total amount ΣD of Sr, Sb, Pb, B, Li, Zr, Mo, W, Ag and P refers to the total content of Sr, Sb, Pb, B, Li, Zr, Mo, W, Ag and P.
[0175] The rest: Zn and impurities
[0176] Zn is preferably contained in a ratio exceeding 50.00%. The plated steel sheet involved in the present embodiment is a Zn-based plated steel sheet with high versatility. By containing a certain amount of Zn or more for the purpose of ensuring sacrificial anode corrosion resistance, the steel sheet is given appropriate sacrificial anode corrosion resistance. For example, even in an environment where the cut end face of more than 1.6 mm is open, as long as the Zn content exceeds 50.0%, sufficient sacrificial anode corrosion resistance can be exhibited on the cut end face, and high corrosion resistance can be maintained. In particular, when the Zn content is less than 50.00%, the corrosion resistance in an alkaline environment is extremely deteriorated, so it is preferred to set the Zn content to more than 50.00%. The Zn content is preferably 55.00% or more, more preferably 60.00% or more, and further preferably 65.00% or more.
[0177] Impurities are components contained in raw materials or components mixed in the manufacturing process, and are components that are not intentionally contained and / or components that are allowed within the range that does not adversely affect the plated steel sheet involved in this embodiment. For example, components other than Fe are sometimes mixed into the plating layer as impurities in trace amounts through atomic diffusion between the steel sheet (base metal) and the plating bath.
[0178] Sn≤Si
[0179] The Si content needs to be greater than the Sn content. If the Si content is less than the Sn content, excess Fe diffuses from the steel sheet into the coating, making it difficult to form the target intermetallic compound. As a result, the corrosion resistance in acidic and alkaline environments deteriorates.
[0180] In addition, Sn and Si in “Sn≤Si” represent the contents of Sn and Si in the plating layer in mass %, respectively.
[0181] 20.0≤Mg / Si
[0182] In addition, regarding the Si content, it is necessary to satisfy 20.0≤Mg / Si. When the Si content is high relative to the Mg content, a large amount of Mg2Si will be formed in the coating, and the corrosion resistance in an acidic environment cannot be fully exerted. In addition, if the Si content is high relative to the Mg content, the formation of Al-Ca-Si compounds is promoted, and the formation of intermetallic compounds (Al2Si) cannot be achieved. 2.15 Zn 1.85 Ca). However, if Mg / Si exceeds 38.0, MgAlSi cannot be formed in the plating layer as described later. Therefore, when MgAlSi is formed in the plating layer, it is preferable to set Mg / Si to 38.0 or less.
[0183] In addition, Mg and Si in "Mg / Si" respectively represent the contents of Mg and Si in the plating layer in mass %.
[0184] 3.00≤Al / Mg≤4.00
[0185] The Al content and the Mg content may also satisfy 3.00≤Al / Mg≤4.00. By satisfying 3.00≤Al / Mg≤4.00, MgAlSi can be formed in the plating layer. In addition, Al and Mg in "Al / Mg" represent the contents of Al and Mg in the plating layer in mass %, respectively.
[0186] The method for identifying the average chemical composition of the coating is described below. First, the coating is stripped and dissolved using an acid containing a corrosion inhibitor that inhibits corrosion of the base metal (steel plate) to obtain an acid solution. Next, the obtained acid solution is measured using ICP emission spectrometry or ICP-MS, thereby obtaining the average chemical composition of the coating. There is no particular limitation on the acid species as long as it is an acid that can dissolve the coating. As long as the area and weight before and after stripping are measured, the coating adhesion amount (g / m 2 ).
[0187] Next, the intermetallic compound contained in the plating layer will be described.
[0188] Since the coating involved in this embodiment is formed by plating a Zn-Al-Mg alloy, the coating contains Zn phase, Al phase, Al-Zn phase, η'-MgZn2 phase and MgZn2 phase as main phases. The corrosion resistance varies with the content of each phase, but by controlling the coating structure such as the content of intermetallic compounds, the difference between the corrosion resistance in an acidic environment below pH 3.5 and the corrosion resistance in an alkaline environment above pH 11.5 can be reduced, and the corrosion resistance can be ensured. Furthermore, as phases other than the main phase, among the above-mentioned intermetallic compounds formed by adding elements other than Zn, Al, and Mg, there are Al-Ca-Si compounds and Mg-Sn compounds.
[0189] Zn phase (η phase: in the Zn-Al phase diagram)
[0190] The Zn phase exists in the coating, mainly in the ternary eutectic structure (Zn / Al / MgZn2 ternary eutectic structure). The Zn phase includes a Zn phase containing less than about 20 mass% Al. The Zn phase in the coating can ensure corrosion resistance in an environment of pH 5.0 to 11.5, with a small amount of corrosion in this range and a high corrosion rate in other ranges.
[0191] Al phase (α phase: in the Zn-Al phase diagram)
[0192] In addition to being present in the plating layer as Al primary crystals in a block form, the Al phase is also contained in a certain amount in the ternary eutectic structure. The Al phase in the plating layer can ensure corrosion resistance in an environment of pH 3.5 to 10.5. The amount of corrosion in this range is small, but the corrosion rate is high in the range outside the pH range of 3.5 to 10.5.
[0193] The Al phase contains about 90 mass % of Al, and the remainder contains Zn. Therefore, the properties of Al are strongly shown, and the Al content is different from that of the Al-Zn phase described later.
[0194] Al-Zn phase (a phase other than α phase and η phase in the Zn-Al phase diagram consisting of Al and Zn) and η'-MgZn2 phase
[0195] The Al-Zn phase is a Zn phase containing about 20% by mass of Al, showing the properties of both the Al phase and the Zn phase. The Al-Zn phase is naturally generated when the coating involved in the present embodiment is made. The Al-Zn phase mentioned here is different from both the Al phase and the Zn phase, and is a phase composed of the two elements Al and Zn.
[0196] The Al-Zn phase is a phase generated by separating the Zn phase from the Al phase during the solidification of the coating, and is mainly formed by the decrease in the solid solubility of the Al phase in the process until it reaches room temperature. If confirmed by the crystal size, it is a structure composed of fine grains of several nm to about 3μm. The reason why the Al-Zn phase shows the performance of both the Zn phase and the Al phase is that it has aggregates of the Zn phase and the Al phase in fine grain units inside it, and does not have any special properties. On the other hand, the adjacency of the grain boundaries and phases with different potentials in the fine phase promotes galvanic reactions, so the corrosion resistance of this phase tends to be inferior to the corrosion resistance of the Al phase (α) and the Zn phase (η) in the coating.
[0197] The Al-Zn phase greatly deteriorates the corrosion resistance in acidic and alkaline environments. However, through appropriate heat treatment (heat treatment for forming η'-MgZn2 phase), the Al-Zn phase can be reduced, eliminating concerns about the deterioration of corrosion resistance in acidic and alkaline environments. Through heat treatment, the Al-Zn phase is reduced and η'-MgZn2 is generated, thereby improving the corrosion resistance in the pH range of 3.5 to 10.5.
[0198] MgZn2 phase
[0199] The MgZn2 phase exists in the coating. In addition to existing in a block form as the MgZn2 phase, it is also contained in a certain amount together with the Al phase in the dendritic structure formed during solidification on the Al-MgZn2 eutectic line and in the ternary eutectic structure (Zn / Al / MgZn2). The MgZn2 phase in the coating can improve the corrosion resistance in the range of pH 5.0 to pH 11.5 and can reduce the amount of corrosion in this range. However, the corrosion rate in the pH range outside of it can hardly be changed. The most common phase in the coating is the MgZn2 phase, so the pH range that can ensure corrosion resistance by changing the composition ratio of the phase is 3.5 to 11.5, and it is difficult to ensure corrosion resistance outside this range.
[0200] The inventors of the present invention sought to improve the coating with the purpose of ensuring corrosion resistance outside the range of pH 3.5 to 11.5, and the results showed that corrosion resistance outside the range of pH 3.5 to 11.5 can be ensured by forming specific intermetallic compounds. In order to determine the content of specific intermetallic compounds in the coating, it is preferred to use X-ray diffraction. Compared with SEM observation, TEM observation, etc., this detection method can obtain average information of the coating, has less selectivity in the measurement site (field of view), and is excellent in quantification. In addition, as long as the measurement conditions are specified, when a specific intermetallic compound is present, the diffraction peak intensity can be obtained at the same angle (2θ) according to a certain ratio, so the internal structure of the coating can be easily inferred.
[0201] The conditions for acquiring the X-ray diffraction image are as follows.
[0202] As an X-ray source, the X-ray diffraction method using Cu as a target is most suitable for obtaining average information of the constituent phases in the coating. As an example of measurement conditions, Cu-Kα rays are used, and the X-ray output is set to a voltage of 40 kV and a current of 150 mA. There is no particular limitation on the X-ray diffraction device, and for example, the sample horizontal type high-power X-ray diffraction device RINT-TTR III manufactured by Rigaku Co., Ltd. can be used.
[0203] Intermetallic Compounds: Al 2.15 Zn 1.85 Ca
[0204] Al 2.15 Zn 1.85 Ca is a substance represented by the database number (ICDD-JCPDS powder diffraction database) 01-078-9051. The Ca-Al-Zn intermetallic compounds are described in detail in (Z, Kristallogr. 224 (2009) 397-406), but form a structure similar to Al4Ca (partial Zn substitution). As these substances with the same structure, such as Al4Ca, Ca 0.5 Zn3.5 、Al3CaZn、Al 2.5 CaZn 1.5 、Al 2.06 CaZn 1.62 、Al2CaZn2、Al 1.75 CaZn 2.25 Substances in which a portion of the Al position is replaced by Zn (0 to 2.25) can also show similar structures, and therefore are expected to have the same properties. However, since these substances are substitution bodies with different atomic radii, they are not necessarily limited to obtaining diffraction peaks at the same position. On the other hand, in this embodiment, since Al is replaced at a specific angle, 2.15 Zn 1.85 Since a diffraction peak is obtained for Ca, it can be treated as a diffraction peak containing the substance.
[0205] The plating composition of this embodiment is suitable for detecting Al 2.15 Zn 1.85 There are three angles of Ca. That is, in the diffraction angle 2θ, it is 22.89° (101 face), 31.67° (103 face), and 43.94° (200 face). Since the diffraction peaks that appear in these diffraction angles do not overlap with the main crystal structure of the coating, it is convenient for quantification and content confirmation. In other words, as long as the diffraction intensity exceeds a certain amount of diffraction peaks at these diffraction angles, it can be said that the target metal oxide is indeed contained.
[0206] However, in the coating studied by the inventors, since the manufacturing conditions of the intermetallic compounds are not necessarily the same as those in the JCPDS data, it can be seen that the diffraction peaks are slightly shifted, and the angle corresponding to 22.89° (101 surface) is 22.90°, the angle corresponding to 31.67° (103 surface) is 31.62°, and the angle corresponding to 43.94° (200 surface) is 44.04°.
[0207] Intermetallic compounds: CaZn2
[0208] This intermetallic compound is represented by (ICDD-JCPDS powder diffraction database) 01-072-5741. As a substitution body, it is assumed that Ca(Al 1.7 Zn 0.3 )(JCPDS card 01-077-6005), but this substitution body is a different substance with a CaAl2 structure as the main component, and the diffraction peak position is different from that of CaZn2, so it is not the subject of this embodiment.
[0209] Be convenient to detect the angle of CaZn2 in the coating composition scope of the present embodiment only has 1 angle, is 33.35 ° (121 faces) (strongest ray) in the diffraction angle 2 θ.The diffraction peak under this diffraction angle is because the main crystalline structure of diffraction peak and coating does not overlap, therefore is convenient to the confirmation of quantification and content.That is to say, as long as obtain the diffraction intensity to exceed a certain amount of diffraction peak under these diffraction angles, it can be said that the metal oxide that contains target really.But, in the coating studied by the inventor, because not necessarily identical with the manufacturing condition of the intermetallic compound of JCPDS data and different, so can see that the diffraction peak is slightly displaced, the diffraction peak as object is preferably 33.35 °.
[0210] These Al 2.15 Zn 1.85 The intermetallic compound of Ca and CaZn2 is an intermetallic compound formed by performing a special heat treatment while forming the plating layer of the plating composition in this embodiment. The above-mentioned intermetallic compound can be formed by replacing Zn originally precipitated as a Zn phase with a part of Al4Ca, and further combining Ca, which is easily incorporated into other intermetallic compounds as Al-Ca-Si, with Al and Zn.
[0211] Furthermore, the properties of these intermetallic compounds were investigated individually, and it was found that the corrosion resistance was improved at pH 3.0 (acidic environment). Since these intermetallic compounds are stable to acid, it is estimated that the corrosion resistance is improved in an acidic environment.
[0212] On the other hand, since the amount of the Zn phase in the plating layer is reduced by containing these intermetallic compounds, the corrosion resistance in an alkaline environment tends to slightly decrease at a pH of 10.0 or more.
[0213] In order to ensure corrosion resistance outside the pH range of 3.5 to 11.5, in the X-ray diffraction pattern of the coating surface obtained by X-ray diffraction of the coating surface using Cu-Kα rays under the conditions of X-ray output of 40 kV and 150 mA, the following formulas (1) to (4) define the Al 2.15 Zn 1.85 In the case of I1 to I3 obtained from the X-ray diffraction peak of Ca and I4 obtained from the X-ray diffraction peak of CaZn2, the following formula (A) must be satisfied:
[0214] [Mathematical formula 6]
[0215]
[0216]
[0217]
[0218]
[0219] 4.05≤I1+I2+I3+I4 (A)
[0220] In the above formulas (1) to (4), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (1) to (4), respectively.
[0221] That is, Imax(22.54~23.30°) in the above formula (1) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 22.54° and 23.30°, and I(22.54°) and I(23.30°) are the X-ray diffraction intensities when the diffraction angle 2θ is at 22.54° and 23.30°, respectively.
[0222] In the above formula (2), Imax(31.00-32.00°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 31.00° and 32.00°, and I(31.00°) and I(32.00°) are the X-ray diffraction intensities when the diffraction angle 2θ is 31.00° and 32.00°, respectively.
[0223] Imax(43.80-44.30°) in formula (3) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 43.80° and 44.30°, and I(43.80°) and I(44.30°) are the X-ray diffraction intensities when the diffraction angle 2θ is at 43.80° and 44.30°, respectively.
[0224] Imax(33.00-33.80°) in formula (4) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 33.00° and 33.80°, and I(33.00°) and I(33.80°) are the X-ray diffraction intensities when the diffraction angle 2θ is 33.00° and 33.80°, respectively.
[0225] Formula (1) is about Al 2.15 Zn 1.85 The formula for the diffraction peak intensity of Ca is the diffraction intensity ratio of the diffraction peak at 2θ=22.89° (101 plane) to the background intensity at 22.89°. The denominator and numerator of formula (1) are described below.
[0226] The denominator of formula (1) (Imax (22.54 ~ 23.30 °)) is the intermetallic compound Al 2.15 Zn 1.85The intensity of the diffraction peak of Ca corresponding to 2θ = 22.90° (101 plane) is the maximum diffraction intensity of the diffraction peak including the background intensity. Due to the measurement error of X-ray diffraction, the diffraction angle 2θ of the (101) plane sometimes deviates from 22.90°, so it is intended to obtain a maximum value between 22.54 and 23.30°.
[0227] The numerator of formula (1) is obtained by calculating the background intensity at a diffraction angle 2θ of 22.90° from the diffraction intensities at 22.54° and 23.30°. Figure 1 As shown in , draw a straight line connecting the diffraction line at 22.54° and the diffraction line at 23.30°. This straight line becomes the baseline of the diffraction peak. Next, find I(23.30°)-I(22.54°). In addition, find the ratio of the difference between the diffraction angle 2θ at 22.54° and 22.90° (0.36°) to the difference between the diffraction angle 2θ at 22.54° and 23.30° (0.76°) (0.36 / 0.76=0.474). Then, calculate the background intensity at the diffraction angle 2θ of 22.89° by the mathematical formula recorded in the denominator of the above formula (1).
[0228] By setting the formula (1) as above, even if measurement errors and background fluctuations occur due to differences in measurement conditions, the intermetallic compound Al can be measured with high accuracy. 2.15 Zn 1.85 The intensity of the diffraction peak of Ca at 2θ=22.90°(101).
[0229] Although equation (1) has been described, equations (2) to (4) and equations (5) to (13) described below are all set based on the same concept as equation (1).
[0230] As shown in the above formula (A), by making the total of I1, I2, I3 and I4 4.05 or more, the corrosion resistance in an acidic environment is improved. It is more preferably 4.10 or more. On the other hand, there is a tendency that the corrosion resistance in an alkaline environment is inferior as the corrosion resistance in an acidic environment is improved, so it is preferred to set the total of I1 to I4 to 4.15 or less.
[0231] Regarding the above formula (A), if the Ca content is high relative to the Si content of the plating layer, Al 2.15 Zn 1.85 Ca and CaZn2, so the Ca / Si ratio can also be set to 0.40 to 0.70. In addition, to satisfy the above formula (A), it is necessary to perform appropriate heat treatment in the manufacturing method while the chemical composition of the plating layer meets the scope of the present invention.
[0232] Intermetallic compound: η'-MgZn2
[0233] η'-MgZn2 is a substance represented by (ICDD-JCPDS powder diffraction database) 01-073-2566. This intermetallic compound is described in detail, for example, in (ACTA, METALLURGICA VOL, 18AUGUST 1970881-890), and is a substance with a crystal structure different from that of MgZn2 as the main phase. There are two diffraction angles 2θ for detecting the intermetallic compound in the composition range of the coating involved in the present embodiment, which are 26.20° (100 face) and 49.22° (-221 face) in the diffraction angle 2θ. The diffraction peaks under these diffraction angles are convenient for quantification and content confirmation because the diffraction peaks do not overlap with the main crystal structure of the coating. In other words, as long as the diffraction intensity exceeds a certain amount of diffraction peaks under these diffraction angles, it can be said that the target metal oxide is indeed contained. However, in the coating studied by the inventors, the manufacturing conditions of the intermetallic compounds are not necessarily the same as those in the JCPDS data, so it can be seen that the diffraction peaks are slightly shifted, and the angle corresponding to 26.20° (100 face) is 26.15°, and 49.22° (-221 face) can remain 49.22°.
[0234] In order to ensure corrosion resistance outside the pH range of 3.5 to 11.5, in the X-ray diffraction pattern of the coating surface obtained by X-ray diffraction of the coating surface using Cu-Kα rays under the conditions of X-ray output of 40 kV and 150 mA, when I5 and I6 obtained from the X-ray diffraction peak of η'-MgZn2 are defined by the following formulas (5) and (6), it is necessary to satisfy the following formula (B):
[0235] [Formula 7]
[0236]
[0237]
[0238] 2.05≤I5+I6 (B)
[0239] In the above formulas (5) and (6), Imax(k°~m°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between k° and m°, I(n°) is the X-ray diffraction intensity when the diffraction angle 2θ is at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (5) and (6), respectively.
[0240] That is to say, Imax(26.00°~26.40°) in the above formula (5) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 26.00° and 26.40°, and I(26.00°) and I(26.40°) are the X-ray diffraction intensities when the diffraction angle 2θ is at 26.00° and 26.40°, respectively.
[0241] In addition, Imax(49.00°~49.60°) in the above formula (6) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 49.00° and 46.60°, and I(49.00°) and I(49.60°) are the X-ray diffraction intensities when the diffraction angle 2θ is 49.00° and 49.60°, respectively.
[0242] As shown in the above formula (B), by making the total of I5 and I6 2.05 or more, the corrosion resistance in an acidic environment at pH 3.0 and an alkaline environment at pH 11.8 is improved. η'-MgZn2 has higher corrosion resistance than ordinary MgZn2. It is preferred that the total of I5 and I6 is a large value, but preferably it is 2.30 or less.
[0243] Regarding the above formula (B), if the Ca content is high relative to the Si content of the coating, it becomes easy to form η'-MgZn2, and the Ca / Si ratio is preferably 0.40 to 0.70. In addition, to satisfy the formula (B), it is necessary to perform appropriate heat treatment in the manufacturing method while the chemical composition of the coating meets the scope of the present invention.
[0244] η'-MgZn2 has the same 2.15 Zn 1.85 The tendency of Ca and Al4Ca to form simultaneously is believed to be due to the complex and special crystal structure of η'-MgZn2 affecting the formation of surrounding intermetallic compounds. By forming these intermetallic compounds simultaneously, the corrosion resistance in both acidic and alkaline environments can be improved.
[0245] Intermetallic Compounds: MgAlSi
[0246] In addition, when the plating layer has a specific component composition and satisfies specific manufacturing conditions, an intermetallic compound MgAlSi can be formed in the plating layer. That is, when the average chemical composition of the plating layer satisfies 20.0≤Mg / Si≤38.0 and 3.00≤Al / Mg≤4.00, and when the temperature region where η'-MgZn2 is easily formed is maintained for a sufficient time, MgAlSi can be formed.
[0247] The intermetallic compound MgAlSi is a substance represented by (ICDD-JCPDS powder diffraction database) 01-074-9054. It is convenient to detect three diffraction angles 2θ of the intermetallic compound in the composition range of the coating involved in this embodiment, which are 24.66° (011 surface), 46.35° (302 surface), and 49.15° (213 surface) in the diffraction angle 2θ. The diffraction peaks under these diffraction angles are convenient for quantification and content confirmation because the diffraction peaks do not overlap with the main crystal structure of the coating. In other words, as long as the diffraction intensity exceeds a certain amount of diffraction peaks under these diffraction angles, it can be said that the target metal oxide is indeed contained. However, in the coating studied by the inventors, the manufacturing conditions of the intermetallic compounds are not necessarily the same as those in the JCPDS data, so it can be seen that the diffraction peaks are slightly shifted, 24.66° (011 surface) can be the original state of 24.66°, the angle corresponding to 46.35° (302 surface) is 46.28°, and 49.15° (213 surface) can be the original state of 49.15°.
[0248] In the X-ray diffraction spectrum of the coating surface measured using Cu-Kα rays under the conditions of X-ray output of 40 kV and 150 mA, when I7 to I9 obtained from the X-ray diffraction peak of MgAlSi are defined by the following formulas (7) to (9), it is preferred that the following formula (C) is satisfied:
[0249] [Mathematical formula 8]
[0250]
[0251]
[0252]
[0253] 3.05≤I7+I8+I9 (C)
[0254] In the above formulas (7) to (9), Imax(k°~m°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between k° and m°, I(n°) is the X-ray diffraction intensity when the diffraction angle 2θ is at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (7) to (9), respectively.
[0255] That is to say, Imax(24.30°~24.90°) in formula (7) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 24.30° and 24.90°, and I(24.30°) and I(24.90°) are the X-ray diffraction intensities when the diffraction angle 2θ is at 24.30° and 24.90°, respectively.
[0256] In the above formula (8), Imax(46.10°~46.40°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 46.10° and 46.40°, and I(46.10°) and I(46.40°) are the X-ray diffraction intensities when the diffraction angle 2θ is at 46.10° and 46.40°, respectively.
[0257] In the above formula (9), Imax(49.00°~49.60°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 49.00° and 49.60°, and I(49.00°) and I(49.60°) are the X-ray diffraction intensities when the diffraction angle 2θ is 49.00° and 49.60°, respectively.
[0258] As shown in the above formula (C), by setting the total of I7, I8 and I9 to 3.05 or more, the corrosion resistance in an alkaline environment exceeding pH 11.5 can be further improved.
[0259] The total of I7, I8, and I9 may be set to 3.10 or less.
[0260] Intermetallic compound: Mg9Sn5
[0261] In addition, when the average chemical composition of the plating layer satisfies 0.01≤Sn and is kept for a sufficient time in a temperature region where η'-MgZn2 is easily formed, Mg9Sn5 is generated in the plating layer.
[0262] The intermetallic compound Mg9Sn5 is a substance represented by (ICDD-JCPDS powder diffraction database) 01-072-8010. Generally, when Sn is contained in a Zn-Al-Mg plated steel sheet, for example, Mg2Sn (00-031-0812 or 01-080-4461) is formed, but the crystal structure of Mg9Sn5 is completely different from these intermetallic compounds.
[0263] It is convenient to detect the diffraction angle 2θ of the intermetallic compound in the composition range of the coating involved in the present embodiment, which is only 23.29 ° (300 faces) in the diffraction angle 2θ. The diffraction peak under this diffraction angle is not overlapped with the main crystal structure of the coating, so it is convenient to confirm the quantification and content. In other words, as long as the diffraction intensity is obtained under this diffraction angle to exceed a certain amount of diffraction peaks, it can be said that the metal oxide containing the target is indeed contained. However, in the coating studied by the inventor, it is different because it is not necessarily the same as the manufacturing conditions of the intermetallic compound of the JCPDS data, so it can be seen that the diffraction peak is slightly displaced, and the angle corresponding to 23.29 ° (300 faces) is 23.40 °.
[0264] In the X-ray diffraction spectrum of the coating surface measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I calculated from the X-ray diffraction peak of Mg9Sn5 is defined by the following formula (10): 10 In the case of, preferably the following formula (D) is satisfied:
[0265] [Mathematical formula 9]
[0266]
[0267] 1.04≤I 10 (D)
[0268] In the above formula (10), Imax(23.10°~23.30°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 23.10° and 23.30°, I(23.10°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.10°, and I(23.30°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.30°.
[0269] As shown in the above formula (D), by making I 10 The pH value is 1.04 or more, which improves the corrosion resistance in an alkaline environment with a pH value exceeding 11.5. Mg9Sn5 has a slightly higher natural potential than Mg9Sn5 because the number of Sn and Mg bonds is smaller than that of Mg2Sn, and thus the corrosion resistance in an alkaline environment is stable.
[0270] You can also use I 10 Set to 1.10 or less.
[0271] Metal oxides
[0272] In addition, if the η'-MgZn2 is kept in a high temperature region for a long time in an atmospheric environment, an oxide film may be formed on the surface of the plated layer. The presence or absence of the oxide film can be changed by heating in a nitrogen atmosphere.
[0273] However, the compounds in the oxide film cannot be fully identified, but in X-ray diffraction, a certain diffraction peak can be shown in the range of diffraction angle 2θ of 0 to 20°, so it is assumed that it is an oxide film caused by metal oxide. The diffraction peaks with diffraction angles 2θ of 10.45°, 12.83°, and 17.36° are easy to quantify and confirm the content because the diffraction peaks do not overlap with the main crystal structure of the coating. In other words, as long as the diffraction intensity exceeds a certain amount at these diffraction angles, it can be said that the target metal oxide is indeed contained.
[0274] In the X-ray diffraction spectrum of the coating surface measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I calculated from the X-ray diffraction peak of the oxide is defined by the following formulas (11) to (13): 11 ~I 13 In the case of, preferably the following formula (E) is satisfied:
[0275] [Formula 10]
[0276]
[0277]
[0278]
[0279] 3.04I 11 +I 12 +I 13 E
[0280] In the above formulas (11) to (13), Imax(k°~m°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between k° and m°, I(n°) is the X-ray diffraction intensity when the diffraction angle 2θ is at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (11) to (13), respectively.
[0281] That is to say, Imax(10.30°~10.70°) in the above formula (11) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 10.30° and 10.70°, and I(10.30°) and I(10.70°) are the X-ray diffraction intensities when the diffraction angle 2θ is at 10.30° and 10.70°, respectively.
[0282] In the above formula (12), Imax(12.30°~13.30°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 12.30° and 13.30°, and I(12.30°) and I(13.30°) are the X-ray diffraction intensities when the diffraction angle 2θ is 12.30° and 13.30°, respectively.
[0283] In the above formula (13), Imax(17.10°~17.50°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 17.10° and 17.50°, and I(17.10°) and I(17.50°) are the X-ray diffraction intensities when the diffraction angle 2θ is 17.10° and 17.50°, respectively.
[0284] As shown in the above formula (E), by making I 11 ,I 12 and I 13The total of is 3.04 or more, which improves the corrosion resistance in an alkaline environment exceeding pH 11.5.
[0285] You can also use I 11 ,I 12 and I 13 The total is set to be 3.10 or less.
[0286] Next, a method for producing a plated steel sheet according to the present embodiment will be described.
[0287] The plated steel sheet involved in this embodiment includes a steel sheet and a plating layer formed on the surface of the steel sheet. Generally, Zn-Al-Mg plating forms the plating layer by metal deposition and solidification reaction. The easiest way to form the plating layer is to form the plating layer on the surface of the steel sheet by hot dip plating, and it can also be formed by a nitriding galvanizing method and a flux method.
[0288] Hereinafter, a case where the plated steel sheet according to the present embodiment is produced by hot-dip plating will be described. The plated steel sheet according to the present embodiment can be produced by either an immersion plating method (batch plating method) or a continuous plating method.
[0289] There are no particular restrictions on the size, shape, surface morphology, etc. of the steel plate to be plated. Any steel plate can be used, whether it is a normal steel plate or stainless steel. Generally, a steel strip for structural steel is most preferred. Beforehand, surface finishing by shot peening or the like can be performed, and even if a Ni, Fe, Zn plating layer of 3 g / m2 or more is attached to the surface, 2 The following metal films or alloy films can be plated without any problem. In addition, the original plate, 150g / m 2 The following galvanized sheet (hot-dip Zn-plated steel sheet or electroplated steel sheet) is preferably subjected to sufficient cleaning by degreasing and pickling as a pre-treatment.
[0290] After the surface of the steel sheet is sufficiently heated and reduced by a reducing gas such as H 2 , the steel sheet is immersed in a plating bath prepared to a predetermined composition.
[0291] The composition of the coating layer can be controlled by the composition of the coating bath in the case of hot dip coating. The coating bath is prepared by mixing pure metals in predetermined amounts, for example, by a dissolution method in an inert atmosphere.
[0292] By immersing the steel sheet whose surface is reduced in a plating bath maintained at a specified concentration, a plating layer having a composition roughly equivalent to that of the plating bath can be formed. When the immersion time is prolonged and it takes a long time to complete solidification, the formation of the interface alloy layer becomes active, so the Fe content in the plating layer sometimes increases. If the bath temperature of the plating bath is lower than 500°C, the reaction between the steel sheet and the plating layer slows down rapidly, so the Fe content contained in the plating layer is usually controlled to be less than 5.0%.
[0293] In order to form the coating, it is preferred to immerse the reduced steel sheet in a coating bath at 500-650°C for a few seconds. On the surface of the reduced steel sheet, Fe diffuses into the coating bath and reacts with the components in the coating bath to form an interface alloy layer (mainly an Al-Fe alloy layer) at the interface between the coating and the steel sheet. Through the interface alloy layer, the steel sheet below the interface alloy layer and the coating above are combined in a metallic chemical manner.
[0294] After the steel sheet is immersed in the plating bath for a specified time, it is lifted out of the plating bath and the plating layer is adjusted to a specified thickness by friction contact with N2 while the metal attached to the surface is in a molten state. The thickness of the plating layer is preferably adjusted to 3 to 80 μm. If converted to the amount of plating attached, it is 10 to 500 g / m 2 (One side). In addition, the thickness of the coating can be adjusted to 5 to 70 μm. If converted into the adhesion amount, it is 20 to 400 g / m 2 (one side).
[0295] After adjusting the coating adhesion amount, the attached molten metal is solidified. The cooling means during the solidification of the coating can be carried out by blowing nitrogen, air or hydrogen-helium mixed gas, or it can be spray cooling or water submersion. The cooling means during the solidification of the coating is preferably spray cooling, more preferably spray cooling containing water in nitrogen. The cooling rate can be adjusted by the proportion of water. When it is desired to form an oxide film on the surface of the coating, it can be manufactured by cooling under an atmospheric environment. On the other hand, in order to avoid the formation of an oxide film, it is preferred to adopt cooling in a furnace where the oxygen concentration is reduced to less than 20ppm, such as N2 replacement, and cooling is implemented by N2 gas.
[0296] As a preferred condition for manufacturing the coating involved in this embodiment, in the cooling when the coating solidifies, the average cooling rate of 500 to 480°C is preferably 30°C / second or more. Since intermetallic compounds such as Al-Ca-Si and Mg2Si are easily formed at 500 to 480°C, these compounds are difficult to precipitate by rapidly cooling this temperature range. Specifically, cooling by means of extremely fast cooling speed in a cooling medium (such as water) with an immersion temperature of about 30°C (about room temperature) has a tendency to improve corrosion resistance in acidic and alkaline environments.
[0297] Next, aging treatment is performed. Al is important in this embodiment. 2.15 Zn 1.85 The formation of intermetallic compounds of Ca, CaZn2, η'-MgZn2, MgAlSi and Mg9Sn5 is carried out by aging treatment based on long-term maintenance at low temperature. The temperature in the aging treatment needs to be strictly limited to the lower limit and the upper limit.
[0298] The temperature range of the aging treatment is preferably set to 80-140°C, and more preferably set to 90-110°C. If the temperature is lower than 80°C, the desired intermetallic compound will not be formed due to the low temperature, and the corrosion resistance will be deteriorated due to the residual Al-Zn phase (about 20% by mass of Al). If the temperature exceeds 140°C, the formation of phases other than the desired intermetallic compound becomes active, and in particular the Al-Zn phase (about 20% by mass of Al) becomes stable, so the corrosion resistance is further deteriorated. In addition, compared with the η'-MgZn2 phase, the MgZn2 phase is stabilized, so that the η'-MgZn2 phase cannot be formed.
[0299] In addition, the holding time of the aging treatment is set to 72 to 750 hours. By aging for more than 72 hours, intermetallic compounds can be formed. In addition, by aging for less than 750 hours, excessive oxidation and corrosion resistance degradation of the coating can be prevented. It is more preferred to set the holding time to more than 250 hours and less than 500 hours.
[0300] The atmosphere for the aging treatment is not particularly limited, and the aging treatment may be performed in the air or in an inert atmosphere such as nitrogen or argon.
[0301] Furthermore, by aging treatment, in addition to the η'-MgZn2 phase, Mg2Zn 11 phase, but no confirmation of the formation of Mg2Zn 11 It can be assumed that Mg2Zn 11 The phase is formed as a byproduct through the transformation to the crystalline structure of η'-MgZn2.
[0302] When the aging treatment is performed, as long as the contents of Mg, Al, and Si satisfy the desired relationship, MgAlSi can be further formed. In addition, when the coating contains a desired amount of Sn, etc., it becomes easy to form Mg9Sn5. In addition, when the aging treatment is performed in an atmospheric environment, metal oxides are formed on the surface.
[0303] Through the above steps, the plating layer of the plated steel sheet defined in this embodiment is completed.
[0304] Various chemical conversion treatments and coating treatments may also be performed after aging treatment. By using the uneven shape of the plated surface to provide a plating layer of Cr, Ni, Au, etc., and further coating, a decorative appearance may be given. In addition, in order to further improve the corrosion resistance, repair paint or spraying treatment may be performed on the welded area, processed part, etc.
[0305] The plated steel sheet involved in this embodiment may also form a covering film on the plated layer. The covering film may be formed into one layer or two or more layers. As the types of covering films directly above the plated layer, for example, chromate covering films, phosphate covering films, and chromate-free covering films may be listed. The chromate treatment, phosphate treatment, and chromate-free treatment for forming these covering films may be performed according to known methods.
[0306] As chromate treatment, there are electrolytic chromate treatment in which a chromate coating is formed by electrolysis; reactive chromate treatment in which a coating is formed by reaction with a raw material and then excess treatment liquid is washed away; and coating chromate treatment in which a coating liquid is applied to a coated object and dried directly without washing to form a coating. Any of these treatments may be used.
[0307] When a coating film exists on the surface of the plated layer, the coating film is completely removed by mechanical removal such as wet polishing so as not to apply heat input to the plated layer, and then the above-mentioned X-ray diffraction is performed.
[0308] Examples of the electrolytic chromate treatment include electrolytic chromate treatment using chromic acid, silica sol, resin (phosphoric acid, acrylic resin, vinyl ester resin, vinyl acetate acrylic emulsion, carboxylated styrene butadiene latex, diisopropanolamine-modified epoxy resin, etc.), and hard silica.
[0309] Examples of the phosphate treatment include zinc phosphate treatment, calcium zinc phosphate treatment, and manganese phosphate treatment.
[0310] Chromate-free treatment is particularly suitable because it has no load on the environment. As chromate-free treatment, there are electrolytic chromate-free treatment that forms a chromate-free coating by electrolysis; reactive chromate-free treatment that forms a coating by reacting with the raw material and then washing away the excess treatment liquid; and coating chromate-free treatment that forms a coating by applying the treatment liquid to the object and drying it directly without washing. Any of these treatments can be used.
[0311] In addition, one or more layers of organic resin covering films may be provided on the covering film directly above the plating layer. The organic resin is not limited to a specific type, and examples thereof include polyester resin, polyurethane resin, epoxy resin, acrylic resin, polyolefin resin, or modified products of these resins. The so-called modified product refers to a resin in which other compounds (monomers and crosslinking agents, etc.) containing functional groups that can react with the functional groups contained in the reactive functional groups contained in the structures of these resins are reacted.
[0312] As such an organic resin, one or more organic resins (unmodified resins) may be mixed and used. In the case where at least one organic resin is present, one or more organic resins obtained by modifying at least one other organic resin may be mixed and used. In addition, any coloring pigment and rust-proof pigment may be contained in the organic resin coating. A water-based resin may be used by dissolving or dispersing in water.
[0313] In addition, in this embodiment, the corrosion resistance in an acidic environment and in an alkaline environment was measured and evaluated as follows.
[0314] Determination method of corrosion resistance in acidic environment
[0315] Pure water was adjusted to pH 3.0 by dropwise addition of dilute sulfuric acid (0.4% by volume) to prepare 1 liter of an acid solution (normal temperature 23° C.).
[0316] The test piece was immersed in the acid solution for 1 second, and then lifted up and placed horizontally in an open drying oven at a temperature of 50° C. and a humidity of less than 10% for 24 hours.
[0317] Consider this as 1 cycle and repeat 60 cycles.
[0318] After 60 cycles, the test piece was immersed in 30 wt% chromic acid (VI) (normal temperature 23°C) to remove the corrosion products formed on the surface of the coating, and then the corrosion loss before and after the test was measured to determine (6-level evaluation) the quality of the corrosion resistance in an acidic environment. As long as the evaluation is D to S+, it can be determined that the corrosion resistance in an acidic environment is excellent.
[0319] The corrosion loss after 60 cycles is less than 5g / m 2 The test piece was judged as "S+" for corrosion resistance on the acid environment side.
[0320] The corrosion loss after 60 cycles is 5g / m 2 Above and below 10g / m 2 The test piece was judged as "S" for corrosion resistance in acidic environment.
[0321] The corrosion loss after 60 cycles is 10g / m 2 Above and below 15g / m 2 The test piece was judged as "A+" for corrosion resistance in acidic environment.
[0322] The corrosion loss after 60 cycles is 15g / m 2 Above and below 20g / m 2 The test piece was judged as "A" for corrosion resistance in acidic environment.
[0323] The corrosion loss after 60 cycles is 20g / m 2 Above and below 30g / m 2 The test piece was judged as "B" for corrosion resistance in acidic environment.
[0324] The corrosion loss after 60 cycles is 30g / m 2 Above and below 40g / m 2 The test piece was judged as "C" for corrosion resistance in acidic environment.
[0325] The corrosion loss after 60 cycles is 40g / m 2 Above and below 50g / m 2 The test piece was judged as "D" for corrosion resistance in acidic environment.
[0326] The corrosion loss after 60 cycles is 50g / m 2 The above test piece was judged as "E" for corrosion resistance in acidic environment.
[0327] Determination method of corrosion resistance in alkaline environment
[0328] Pure water was adjusted to pH 11.8 by dropwise addition of aqueous ammonia (3% by volume) to prepare 1 liter of an alkaline solution (normal temperature 23° C.).
[0329] The test piece was immersed in the alkaline solution for 1 second, and then lifted up and placed horizontally in an open drying oven at a temperature of 50° C. and a humidity of less than 10% for 24 hours.
[0330] Consider this as 1 cycle and repeat 60 cycles.
[0331] After 60 cycles, the test piece was immersed in 30 wt% chromic acid (VI) (normal temperature 23°C) to remove the corrosion products formed on the surface of the coating, and the corrosion loss before and after the test was measured to determine the quality of the corrosion resistance in an alkaline environment. As long as the evaluation is D to S+, it can be judged that the corrosion resistance in an alkaline environment is excellent.
[0332] The corrosion loss after 60 cycles is less than 5g / m 2 The test piece was judged as "S+" for corrosion resistance in alkaline environment
[0333] The corrosion loss after 60 cycles is 5g / m 2 Above and below 10g / m 2 The test piece was judged as "S" for corrosion resistance in alkaline environment
[0334] The corrosion loss after 60 cycles is 10g / m 2 Above and below 15g / m 2 The test piece was judged as "A+" for corrosion resistance in alkaline environment.
[0335] The corrosion loss after 60 cycles is 15g / m 2 Above and below 20g / m 2 The test piece was judged as "A" for corrosion resistance in alkaline environment.
[0336] The corrosion loss after 60 cycles is 20g / m 2 Above and below 30g / m 2 The test piece was judged as "B+" for corrosion resistance in alkaline environment.
[0337] The corrosion loss after 60 cycles is 30g / m 2 Above and below 35g / m 2 The test piece was judged as "B" for corrosion resistance in alkaline environment.
[0338] The corrosion loss after 60 cycles is 35g / m 2 Above and below 40g / m 2 The test piece was judged as "C" for corrosion resistance in alkaline environment
[0339] The corrosion loss after 60 cycles is 40g / m 2 Above and below 50g / m 2 The test piece was judged as "D" for corrosion resistance in alkaline environment.
[0340] The corrosion loss after 60 cycles is 50g / m 2 The above test piece was judged as "E" for corrosion resistance in alkaline environment.
[0341] Example
[0342] Next, the effects of one embodiment of the present invention are described in more detail by way of examples, but the conditions in the examples are one condition example adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this one condition example. The present invention may adopt various conditions as long as it does not deviate from the gist of the present invention and achieves the purpose of the present invention.
[0343] The plated steel sheets shown in Table 2A-1 to Table 6B-2 were produced and their properties were evaluated.
[0344] Each plating bath was prepared by mixing pure metals. The composition of the plating alloy was adjusted by adding Fe powder after the bath was prepared so that the Fe concentration would not increase during the test.
[0345] In addition, the value described as "0" in the table|surface shows that it is lower than the detection limit value of 0.005% in ICP.
[0346] As the plated steel plate, a steel plate (1.6 mm) with a size of 180×100 was used. Furthermore, a cold-rolled steel plate shown in JIS G3141: 2021 was used. In the formation of the coating, an intermittent hot-dip plating simulator (manufactured by our company) was used. A K thermocouple was installed on a part of the plated steel plate, and annealing was performed by heating to 800°C and maintaining in an atmosphere of N295vol%-H25vol% mixed gas to fully reduce the surface of the steel plate. Then, it was immersed in a plating bath with a bath temperature of 500-650°C for 3 seconds, and then lifted, and the thickness of the coating was adjusted to 25-30μm by friction contact with N2 gas.
[0347] The heat treatment after the N2 gas friction contact was performed in the following three cooling modes. In addition, it is described as "plating method" in Table 1A-1 to Table 1B-2.
[0348] A: After N2 gas friction contact, cooling is performed by water immersion at 500°C (cooling rate 100°C / sec or more: reaching water temperature (about 30°C) within 2 seconds)
[0349] B: After N2 gas friction contact, N2 gas was blown at an average cooling rate of 40°C / sec at 500-480°C, and then N2 gas was blown at an average cooling rate of 10-20°C / sec at 480-50°C for cooling.
[0350] C: After N2 gas friction contact, N2 gas is sprayed to cool at an average cooling rate of 10 to 20°C / sec at 500 to 50°C.
[0351] Then, each sample was subjected to heat treatment (aging treatment) as shown in Table 1A-1 to Table 1B-2. In Table 1A-1 to Table 1B-2, "atmosphere" indicates the atmosphere during aging treatment, "reheating temperature" indicates the heating temperature during aging treatment, and "time" indicates the holding time during aging treatment.
[0352] The obtained plated steel sheet was cut into 20 mm squares, and the X-ray diffraction pattern of the plated surface was analyzed using a sample horizontal type high-power X-ray diffractometer (model RINT-TTR III) manufactured by Rigaku Co., Ltd. Specifically, Cu-Kα rays were used, the X-ray output was 40 kV and 150 mA, and the copper target, goniometer TTR (horizontal goniometer), Kβ filter slit width 0.05 mm, length limit slit width 2 mm, light receiving slit width 8 mm, light receiving slit double opening were specified, and as measurement conditions, the scanning speed was specified to be 5 deg. / min, the step length was 0.01 deg, and the scanning axis was 2θ (5 to 90°) to perform the measurement, thereby obtaining the X-ray diffraction intensity at each angle.
[0353] The corrosion resistance in an acidic environment and an alkaline environment was measured and evaluated as follows. The results are shown in Table 7A-1 to Table 7B-2.
[0354] Determination method of corrosion resistance in acidic environment
[0355] Pure water was adjusted to pH 3.0 by dropping dilute sulfuric acid (0.4 volume %) to prepare 1 liter of acid solution (normal temperature 23°C). Next, the test piece was immersed in the acid solution for 1 second, and after being lifted up, it was placed horizontally in an open drying oven at a temperature of 50°C and a humidity of less than 10% for 24 hours. This was regarded as 1 cycle and repeated 60 cycles. After 60 cycles, the test piece was immersed in 30 wt% chromic acid (VI) (normal temperature 23°C) to remove the corrosion products formed on the surface of the coating, and the corrosion loss before and after the test was measured to determine (6-level evaluation) the quality of the corrosion resistance in an acidic environment.
[0356] When the evaluation is D to S+, the corrosion resistance in an acidic environment is excellent and is judged as acceptable. On the other hand, when the evaluation is E, the corrosion resistance in an acidic environment is poor and is judged as unacceptable.
[0357] The corrosion loss after 60 cycles is less than 5g / m 2 The test piece was judged as "S+" for corrosion resistance on the acid environment side.
[0358] The corrosion loss after 60 cycles is 5g / m 2 Above and below 10g / m 2 The test piece was judged as having corrosion resistance "S" on the acid environment side.
[0359] The corrosion loss after 60 cycles is 10g / m 2 Above and below 15g / m 2 The test piece was judged as "A+" for corrosion resistance in acidic environment.
[0360] The corrosion loss after 60 cycles is 15g / m 2 Above and below 20g / m 2 The test piece was judged as "A" for corrosion resistance in acidic environment.
[0361] The corrosion loss after 60 cycles is 20g / m 2 Above and below 30g / m 2 The test piece was judged as "B" for corrosion resistance in acidic environment.
[0362] The corrosion loss after 60 cycles is 30g / m 2 Above and below 40g / m 2 The test piece was judged as "C" for corrosion resistance in acidic environment.
[0363] The corrosion loss after 60 cycles is 40g / m 2 Above and below 50g / m 2 The test piece was judged as "D" for corrosion resistance in acidic environment.
[0364] The corrosion loss after 60 cycles is 50g / m 2 The above test piece was judged as "E" for corrosion resistance in acidic environment.
[0365] Determination method of corrosion resistance in alkaline environment
[0366] Prepare 1 liter of alkaline solution (normal temperature 23°C) by adding ammonia water (3% by volume) to adjust the pure water to pH 11.8. Next, immerse the test piece in the alkaline solution for 1 second, lift it up, and place it horizontally in an open drying oven with a temperature of 50°C and a humidity of less than 10% for 24 hours. This is considered as 1 cycle and repeated 60 times. After 60 cycles, immerse the test piece in 30% by weight chromic acid (VI) (normal temperature 23°C) to remove the corrosion products formed on the surface of the coating, measure the corrosion loss before and after the test, and judge the quality of corrosion resistance.
[0367] The corrosion loss after 60 cycles is less than 5g / m 2 The test piece was judged as "S+" for corrosion resistance in alkaline environment.
[0368] The corrosion loss after 60 cycles is 5g / m 2 Above and below 10g / m 2 The test piece was judged as having corrosion resistance "S" on the alkaline environment side.
[0369] The corrosion loss after 60 cycles is 10g / m 2 Above and below 15g / m 2 The test piece was judged as "A+" for corrosion resistance in alkaline environment.
[0370] The corrosion loss after 60 cycles is 15g / m 2 Above and below 20g / m 2 The test piece was judged as "A" for corrosion resistance in alkaline environment.
[0371] The corrosion loss after 60 cycles is 20g / m 2 Above and below 30g / m 2 The test piece was judged as "B+" for corrosion resistance in alkaline environment.
[0372] The corrosion loss after 60 cycles is 30g / m 2 Above and below 35g / m 2 The test piece was judged as "B" for corrosion resistance in alkaline environment.
[0373] The corrosion loss after 60 cycles is 35g / m 2 Above and below 40g / m 2 The test piece was judged as "C" for corrosion resistance in alkaline environment
[0374] The corrosion loss after 60 cycles is 40g / m 2 Above and below 50g / m 2 The test piece was judged as "D" for corrosion resistance in alkaline environment.
[0375] The corrosion loss after 60 cycles is 50g / m 2 The above test piece was judged as "E" for corrosion resistance in alkaline environment.
[0376] In the following test examples, the chemical composition of the coating is within the scope of the present invention, the manufacturing conditions are within the preferred range, and the corrosion resistance is excellent in both acidic and alkaline environments. In addition, in the coatings of these test examples, the main phase contains Zn phase, Al phase, Al-Zn phase, η'-MgZn2 phase and MgZn2 phase.
[0377] No.2~16, 18~28, 30~33, 35, 37, 42, 43, 45, 48~50, 52~56, 58, 60, 63, 65, 67, 69, 71, 75, 76, 78, 79, 81, 82, 84, 85, 87, 88, 90, 91, 93, 94, 96, 97, 99, 100, 102, 103, 105, 109~114, 117, 118, 120~124, 128~132.
[0378] On the other hand, in the following test examples, the chemical composition of the plating layer was outside the scope of the present invention and did not satisfy the formula (A) and the formula (B). Therefore, it was evaluated as E in both the acidic environment and the alkaline environment, and the corrosion resistance was inferior.
[0379] No.1, 17, 29, 34, 36, 38~41, 44, 46, 47, 51, 57, 59, 61, 62, 64, 66, 68, 70, 72~74, 77, 80, 83, 86, 89, 92, 95, 98, 101, 104, 106, 136, 137.
[0380] In addition, although the chemical composition of the plating layer in the following test examples is within the scope of the present invention, since the manufacturing conditions deviate from the preferred range, formula (A) and formula (B) are not satisfied, and the evaluation is E in both acidic and alkaline environments, and the corrosion resistance is inferior.
[0381] No.107, 108, 115, 116, 119, 125~127, 133~135, 138.
[0382] Table 1A-1
[0383]
[0384] The underline indicates that the conditions are outside the range of the preferred production conditions.
[0385] Table 1A-2
[0386]
[0387] The underline indicates that the conditions are outside the range of the preferred production conditions.
[0388] Table 1B-1
[0389]
[0390] The underline indicates that the conditions are outside the range of the preferred production conditions.
[0391] Table 1B-2
[0392]
[0393] The underline indicates that the conditions are outside the range of the preferred production conditions.
[0394] Table 2A-1
[0395]
[0396] The underline indicates outside the scope of the present invention.
[0397] Table 2A-2
[0398]
[0399] The underline indicates outside the scope of the present invention.
[0400] Table 2B-1
[0401]
[0402] The underline indicates outside the scope of the present invention.
[0403] Table 2B-2
[0404]
[0405] The underline indicates outside the scope of the present invention.
[0406] Table 3A-1
[0407]
[0408] The underline indicates outside the scope of the present invention.
[0409] Table 3A-2
[0410]
[0411] The underline indicates outside the scope of the present invention.
[0412] Table 3B-1
[0413]
[0414] The underline indicates outside the scope of the present invention.
[0415] Table 3B-2
[0416]
[0417] The underline indicates outside the scope of the present invention.
[0418] Table 4A-1
[0419]
[0420] The underline indicates outside the scope of the present invention.
[0421] Table 4A-2
[0422]
[0423] The underline indicates outside the scope of the present invention.
[0424] Table 4B-1
[0425]
[0426] The underline indicates outside the scope of the present invention.
[0427] Table 4B-2
[0428]
[0429] The underline indicates outside the scope of the present invention.
[0430] Table 5A-1
[0431]
[0432] The underline indicates outside the scope of the present invention.
[0433] Table 5A-2
[0434]
[0435] The underline indicates outside the scope of the present invention.
[0436] Table 5B-1
[0437]
[0438] The underline indicates outside the scope of the present invention.
[0439] Table 5B-2
[0440]
[0441] The underline indicates outside the scope of the present invention.
[0442] Table 6A-1
[0443]
[0444] Table 6A-2
[0445]
[0446] Table 6B -
[0447]
[0448] Table 6B-2
[0449]
[0450] Table 7A-1
[0451]
[0452] Table 7A-2
[0453]
[0454] Table 7B-1
[0455]
[0456] Table 7B-2
[0457]
Claims
1. A plated steel sheet having a plated layer on the surface of the steel sheet, in, The average chemical composition of the plating layer contains, by mass%, Al: more than 15.0% and less than 30.0%, Mg: more than 5.0% and less than 15.0%, Sn: 0~0.70%, Bi: 0~0.35% In: 0~0.35%, Ca: 0.03-0.60%, Y:0~0.30%、 La: 0~0.30% Ce: 0~0.30%, Si: 0.01-0.75%, Cr:0~0.25%、 Ti: 0~0.25%, Ni: 0-1.00%, Co: 0-0.25%, V:0~0.25%、 Nb: 0~0.25%, Cu: 0-0.25%, Mn: 0~0.25%, Fe: 0-5.0%, Sr:0~0.5%、 Sb: 0-0.5%, Pb: 0~0.5%, B:0~0.5%、 Li: 0~0.5% Zr:0~0.5%、 Mo: 0~0.5%, W:0~0.5%、 Ag: 0-0.5%, and P:0~0.5%, The remainder includes Zn and impurities; The total amount ΣA of Sn, Bi and In is 0% or more and less than 0.75%, The total amount of Ca, Y, La and Ce ΣB is 0.03 to 0.60%, The total amount ΣC of Cr, Ti, Ni, Co, V, Nb, Cu and Mn is 0-1.00%, satisfying Sn≤Si and 20.0≤Mg / Si; In the X-ray diffraction pattern of the surface of the coating layer measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the following formulas (1) to (6) define the X-ray diffraction patterns of Al 2.15 Zn 1.85 In the case of I1 to I3 obtained from the X-ray diffraction peak of Ca, I4 obtained from the X-ray diffraction peak of CaZn2, and I5 and I6 obtained from the X-ray diffraction peak of η'-MgZn2, the following formulas (A) and (B) are satisfied: [Mathematical formula 1] 4.05≤I1+I2+I3+I4 (A) 2.05≤I5+I6 (B) In the above formulas (1) to (6), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (1) to (6), respectively.
2. The plated steel sheet according to claim 1, wherein: The average chemical composition of the coating satisfies 20.0≤Mg / Si≤38.0 and 3.00≤Al / Mg≤4.00, In the X-ray diffraction spectrum of the surface of the coating measured using Cu-Kα rays at an X-ray output of 40 kV and 150 mA, when I7 to I9 obtained from the X-ray diffraction peaks of MgAlSi are defined by the following equations (7) to (8), the following equation (C) is satisfied: [Mathematical formula 2] 3.05≤I7+I8+I9 (C) in, In the above formulas (7) to (9), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in formulas (7) to (9), respectively.
3. The plated steel sheet according to claim 1, wherein: The average chemical composition of the coating satisfies 0.01%≤Sn, In the X-ray diffraction spectrum of the surface of the coating measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I calculated from the X-ray diffraction peak of Mg9Sn5 is defined by the following formula (10): 10 In the case of, the following formula (D) is satisfied: [Mathematical formula 3] 1.04≤I 10 (D) Wherein, in the formula (10), Imax(23.10~23.80°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 23.10 and 23.80°, I(23.10°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.10°, and I(23.80°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.80°.
4. The plated steel sheet according to claim 2, wherein: The average chemical composition of the coating satisfies 0.01%≤Sn, In the X-ray diffraction spectrum of the surface of the coating measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I calculated from the X-ray diffraction peak of Mg9Sn5 is defined by the following formula (10): 10 In the case of, the following formula (D) is satisfied: [Formula 4] 1.04≤I 10 (D) Wherein, in the formula (10), Imax(23.10~23.80°) is the maximum value of the X-ray diffraction intensity when the diffraction angle 2θ is between 23.10 and 23.80°, I(23.10°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.10°, and I(23.80°) is the X-ray diffraction intensity when the diffraction angle 2θ is 23.80°.
5. The plated steel sheet according to any one of claims 1 to 4, wherein In the X-ray diffraction spectrum of the surface of the coating layer measured using Cu-Kα radiation at an X-ray output of 40 kV and 150 mA, the I calculated from the X-ray diffraction peak of the metal oxide is defined by the following formulas (11) to (13): 11 ~I 13 In the case of, the following formula (E) is satisfied: [Formula 5] 3.04≤I 11 +I 12 +I 13 (E) In the above formulas (11) to (13), Imax(k~m°) is the maximum value of the X-ray diffraction intensity at the diffraction angle 2θ between k and m°, I(n°) is the X-ray diffraction intensity at the diffraction angle 2θ at n°, and k, m, and n are the diffraction angles 2θ shown in the above formulas (11) to (13), respectively.
6. The plated steel sheet according to any one of claims 1 to 4, wherein The plating layer contains a Zn phase, an Al phase, an Al-Zn phase, an η'-MgZn2 phase and a MgZn2 phase.
7. The plated steel sheet according to claim 5, wherein: The coating contains Zn phase, Al phase, Al-Zn phase, η'-MgZn2 phase and MgZn2 phase.
